Investigation of the Hysteresis Performance of Multi-Story Y-Shaped Eccentrically Bare Braced Steel Frame with Block Slit Damper (BSD) - Chen Zhou; Haibo Wen; Jing Zhao; Lizhong Jiang; Xiaodong Xu; Hong Zheng; Yuxiao Tian; Muhua Liang; Xiyao Wang; Hai Zhang (Buildings, 2025)
This paper investigated the hysteresis performance of multi-story Y-shaped eccentrically bare braced steel frames with block slit dampers (BSDs). After validating existing models through finite element (FE) analysis, an FE model of Y-shaped eccentrically bare braced steel frames (YEBFs) with BSD (BSD-YEBFs) was established. The influences of different types of BSDs on the hysteresis performance of YEBFs were subsequently analysed, as were the seismic performances of YEBFs with BSD (BSDF) and traditional Y-shaped eccentrically bare braced steel frames (TEBF) under cyclic loading, including the stress failure mode, hysteresis curve, stiffness, strength, and energy dissipation capacity. The results showed that: (1) compared with those of BASE-Y, the ductility coefficients of YEBFs with one level BSD (BSD-1) and two level BSD (BSD-2) increased by 59.57% and 39.47%, respectively, and the lateral bearing capacity decreased by 3.26% and 2.78%, respectively. (2) Compared with those of TEBF, the yield bearing capacity and ultimate bearing capacity of BSDF increased by 3.13% and 11.12%, respectively, and the ductility coefficient increased by 56.7%. Moreover, BSDF possesses higher initial stiffness and more sustained energy dissipation capabilities.